Hemangioblastoma Instead of Renal Cell Carcinoma Plays a Major Role in the Unfavorable Overall Survival of Von Hippel-Lindau Disease Patients - Zhou, Bowen; Wang, Jiangyi; Liu, Shengjie; Peng, Xiang; Hong, Baoan; Zhou, Jingcheng; Ma, Kaifang; Zhang, Jiufeng; Cai, Lin; Gong, Kan (Frontiers in Oncology, 2019)
Von Hippel-Lindau (VHL) disease is a hereditary cancer syndrome characterized by poor survival. The effect of the involvement of each organ on survival remains unclear. Our study aimed to study the effect of the involvement of each organ on survival in VHL disease patients. We retrospectively analyzed 336 patients from 125 families. The onset age was compared between different groups using Mann-Whitney U test and Kruskal-Wallis test. Univariate and multivariate time-dependent Cox regression analyses were conducted to evaluate how survival was influenced by the involvement of each organ. The median survival time for VHL disease patients was 66 years. The onset age was earlier in the central nervous system (CNS) group than in the abdominal group. The involvement of central nervous system hemangioblastoma (CHB) and retinal hemangioblastoma (RA) were independent risk factors for overall survival. The involvement of renal cell carcinoma (RCC) was not a significant risk factor for overall survival. Only RA was a risk factor for CHB-specific survival. This study analysed the relationship between organ involvement and survival of VHL patients. This may help guide future genetic counselling and clinical decision-making.